Soil moisture measurement tools using SHT11 sensors based on the Internet of Things - Karinia, Yolanda; Violita, Violita; Tarigan, Heron; Sudiar, Nofi Yendri; Yulkifli, Yulkifli (INVOTEK: Jurnal Inovasi Vokasional dan Teknologi, 2021)
One of the important factors for living things and also the weather element is soil moisture. Observations of weather elements have been carried out used according to future needs. Soil moisture has been using to manage weather forecasts, early warning of drought, water resources, and irrigation scheduling. Due to the development of sensors in the electronics world, various digital measuring instruments where is founded to make it easier to measure soil moisture. This article describes the manufacture of a soil moisture meter and the results of the performance specifications of the humidity measurement system with the internet of things-based SHT11 sensor. This instrument uses an SHT11 sensor is used for the humidity sensor and soil temperature, Nodemcu ESP8266 is used as Internet access to transmit to thingspeak, data save in the micro SD memory.